Three Prayers and Sermons - Swift, Jonathan, 1667-1745; Morley, Henry, 1822-1894 (Salt Lake City, UT : Project Gutenberg, 2003)
"Three Prayers and Sermons by Jonathan Swift" is a religious text comprised of prayers and sermons authored by Jonathan Swift, a prominent satirist and cleric of the early 18th century. The book is likely dated to the early 1700s, a period when Swift was active in the Anglican church and engaged in various literary pursuits. The content addresses themes of faith, morality, and the human condition, showcasing Swift's reflections on spirituality and the responsibilities of individuals within a religious framework. The collection includes three heartfelt prayers Swift composed for his close friend Stella during her final illness, emphasizing themes of hope, repentance, and divine grace. Additionally, the volume features sermons that critique societal norms, such as the expectation of mutual respect and humility in relationships and the importance of being attentive during worship. Swift employs a direct and sometimes satirical tone to address both personal and societal failings, ultimately urging a return to genuine faith and earnestness in one's spiritual practice. The work serves as both a personal expression and a broader commentary on human behavior in relation to divine expectations. (This is an automatically generated summary.)
I. On mutual subjection. $1 (BII. On conscience. $1 (BIII. On the Trinity.s
Release date is 2003-12-01
Transcribed from the 1889 George Routledge and Sons (3z(BThe Tale of a Tub and Other Works(3y (Bedition by Stephen Rice. Additional proofing by David Prices
Keywords: Church of England -- Sermons; Sermons, English -- 18th century; Obedience; Conscience; Trinity -- Early works to 1800